solve this problem . It is from A.P 10th class
Attachments:
![](https://hi-static.z-dn.net/files/df6/a7af5eeefaa376dc6916a18ad3d34721.jpg)
Answers
Answered by
0
write the question properly .can't understand your handwriting
Answered by
1
given = ![a_{12} = 81 a_{12} = 81](https://tex.z-dn.net/?f=+a_%7B12%7D+%3D+81)
A.P = x-1, x-2, x+3.......
answer,
a = x-1
d = x-2 - (x-1)
= -1
a + 11d = 81
(x-1) + 11(-1) = 81
x = 81+12 =93
![a_{n} = a + (n-1)d a_{n} = a + (n-1)d](https://tex.z-dn.net/?f=+a_%7Bn%7D+%3D+a+%2B+%28n-1%29d)
=(x-1) + n-1(-1)
= 92-n +1
![a_{n} = 93 - n a_{n} = 93 - n](https://tex.z-dn.net/?f=+a_%7Bn%7D+%3D+93+-+n)
now,
![S_{n} = \frac{n}{2} (a + l) S_{n} = \frac{n}{2} (a + l)](https://tex.z-dn.net/?f=+S_%7Bn%7D+%3D+%5Cfrac%7Bn%7D%7B2%7D+%28a+%2B+l%29)
=![\frac{n}{2} ( 92 + 93 - n) \frac{n}{2} ( 92 + 93 - n)](https://tex.z-dn.net/?f=+%5Cfrac%7Bn%7D%7B2%7D+%28+92+%2B+93+-+n%29)
.... this is the last answer
I hope this will help you!!!!
A.P = x-1, x-2, x+3.......
answer,
a = x-1
d = x-2 - (x-1)
= -1
a + 11d = 81
(x-1) + 11(-1) = 81
x = 81+12 =93
=(x-1) + n-1(-1)
= 92-n +1
now,
=
I hope this will help you!!!!
Similar questions